Adaptive Control of Atomic Force Microscope for Surface-Profile Estimation - Apiwattanalunggarn, Nyesunthi (Journal of Applied Nonlinear Dynamics, 2026)
This paper describes a methodology for designing an adaptive tracking controller of an atomic force microscope to estimate a surface proﬁle of a sample. A microbeam of the atomic force microscope is modeled as an Euler-Bernoulli beam with single mode considered. A tip-sample interaction force used here is a piecewise function described by the attractive van der Waals force and the repulsive Derjaguin-Muller-Toporov force which can represent the indentation made by a tip of the microbeam into the sample surface. The adaptive-tracking controllers for both regions are designed based on adaptive control Lyapunov functions. With the driving and measured signals, the controlled acceleration is generated and superimposed onto the harmonic excitation and the estimated surface proﬁle is obtained. If the tip of the microbeam taps harder on the sample surface, the more estimation error is obtained. To reduce the estimated surface-proﬁle error, the regression model needs more higher-order terms to approximate the repulsive Derjaguin-Muller-Toporov force.